包含SASP调节剂和衰老衰减剂的组合物及其用于调节细胞衰老的用途 (2023)
本文描述了用于调节细胞的细胞衰老或诱导细胞中衰老相关分泌表型(SASP)的组合物和方法。该方法通常包括将IRE1a的水平或活性调节为控制细胞衰老和诱导SASP的平均值。还描述了用于治疗和预防眼血管疾病的方法，其包括使受试者眼中的细胞与双胍化合物以及包含双胍化合物的眼用组合物接触。 Described herein are compositions and methods for modulating cellular senescence of a cell or induction of the senescence-associated secretory phenotype (SASP) in a cell. The methods generally comprise modulating the level or activity of IRE1a as a mean to control cellular senescence and induction of the SASP. Also described are methods for treating and preventing ocular vascular diseases comprising contacting cells in an eye of a subject with a biguanide compound and ophthalmic compositions comprising a biguanide compound.